RIPK3 collaborates with RIPK1 to inhibit MAVS-mediated signaling during black carp antiviral innate immunity. Issue 115 (August 2021) - Dai, Yuhan; Cao, Yingyi; Chen, Zhaoyuan; Huang, Jiayi; Xiao, Jun; Zou, Jun; Feng, Hao
Abstract: Both the activation and attenuation of MAVS/IFN signaling are critical for host defensing against viral infection and thus lead to an elaborate regulation of MAVS-mediated signaling. However, the regulatory mechanisms concerning MAVS/IFN signaling in teleost fish are not well understood. RIPK3 has been identified as a key regulator of necroptosis, apoptosis, and inflammatory signaling in human and mammals. Here we report the identification of the RIPK3 homologue from black carp Mylopharyngodon piceus (bcRIPK3) and describe its role in regulating MAVS/IFN signaling. qPCR results demonstrated that bcRIPK3 was transcriptionally activated in response to poly (I:C) or LPS stimulation. Immunoblot assay and immunofluorescent staining assay showed that bcRIPK3 was a cytosolic protein with molecular weights of 47 kDa. Like its mammalian counterparts, bcRIPK3 exhibited a conserved function in inducing cell death. The reporter assay and plaque assay showed that overexpression of bcRIPK3 restricted bcMAVS-activated transcription of the interferon promoters of black carp and zebrafish, and suppressed bcMAVS-mediated antiviral activity. Notably, EPC cells co-expressing bcRIPK3, bcRIPK1 and bcMAVS presented much attenuated antiviral activity than the cells co-expressing bcRIPK3 and bcMAVS; and the subsequent co-IP assay identified the interaction between bcRIPK3 and bcRIPK1. Our findings collectively elucidate for the first time in teleost that black carp RIPK3 interacts with RIPK1 to inhibit MAVS-mediated antiviral signaling. Highlights: bcRIPK3 suppresses bcMAVS-mediated IFN production and antiviral activity. bcRIPK3 interacts with bcRIPK1. bcRIPK3 and bcRIPK1 show synergistic effects on the inhibition of bcMAVS-mediated signaling.